Impact of Sanctions on Industry Indices - E. A. Fedorova; A. R. Nevredinov (Финансы: теория и практика)
Anti-Russian sanctions have an additional impact on Russian companies. Due to the rapid change in the situation and the development of information situations, it is becoming difficult for investors to make investment decisions. This determines the relevance of the study, the purpose of which is to determine the impact of information about sanctions on stock indices of lower industries. The empirical basis for the study of indicators includes 67 thousand news items from the Interfax platform for 2014–2023. The following were used as control measures: the price of Brent oil futures, the dollar-ruble exchange rate, and the RUONIA benchmark interest rate. The indices of MOEKEU (electric power industry), MOEKS (chemistry and oil chemistry), MOEKOG (oil and gas) are considered. All data were obtained for the period from 01.01.2014 to 31.12.2023. The research methodology is based on mathematical modeling using the BERTopic topic modeling algorithm. Four main topics of sanctions were identified: “Anti-sanctions policy and sanctions evasion”, “Western sanctions”, “Sanctions against industry-specific companies”, “Financial market”. The impact on industry indices was assessed using the random forest algorithm and GARCH analysis. It has been proven that sanctions have less impact on the indices of those industries that are sufficiently autonomous in Russia. Investors pay attention to entrepreneurial topic, and not to the sanctions rhetoric. Negative information can lead to their irrational behavior. The period of maximum impact of sanctions was also determined: a month from the date of release of information about the introduction of sanctions. As a result, the following conclusions were made: 1) when referring to industry indices, not all news about sanctions is taken into account, as are messages on the topic of manufacturers, taking into account industry specifics; 2) for the index of the chemical and petrochemical sector of the greatest initiative, which has an anti-sanction policy index; 3) the energy plumbing sector is less developed. The results of the study can be useful for determining investment directions